Nanosilica and jasmonic acid as alternative methods for control Tuta absoluta (Meyrick) in tomato crop under field conditions. (26th August 2016) - Fouad, Hany Ahmed; El-Gepaly, Hosam Mohamed Khalil Hammam; Fouad, Osama Ahmed
Abstract: Recently, Tuta absoluta became one of the major pests that attack commercial tomato globally. Field test was done to evaluate the effect of different concentrations of nanosilica (NS) and jasmonic acid (JA), and compared them with indoxacrb (recommended insecticide) on reduction of damage rate caused by T. absoluta larvae under field conditions. Nanosilica (600 ppm) and indoxacrb (0.25 cm 3 /L) had the highest efficiency to reduce the rate of mines in the leaves. Jasmonic acid at rate 1.141 μM/plant showed a good reduction of number of fruits damaged. Nanosilica with 600 ppm concentration and Jasmonic acid at rate 1.141 μM/plant is used to control T. absoluta in the field.